Duration and seriousness of running mechanics alterations after maximal cycling in triathletes. Influence of the performance level - Millet, G. P.; Millet, G. Y.; Candau, R. B. (The Journal of Sports Medicine and Physical Fitness, 2001)
Non-experienced triathletes use to complain about the difficulty to run after cycling. We tested the hypothesis that elite triathletes have lower and/or shorter alterations in running mechanics following a maximal cycling exercise than their less efficient counterparts. METHODS: The mechanical alterations in running after exhaustive cycling exercise were studied in eight elite (E) and 18 middle-level (M) triathletes. Before and after maximal cycling exercise, the subjects completed two 7-min runs on a treadmill at a velocity corresponding to that sustained during a triathlon. External mechanical cost was quantified during the first and last minute of each run from displacements of the centre of mass using a kinematic arm. RESULTS: The effect of cycling on the potential, kinetic and mechanical costs (respectively, 7.1+/-6.0% and 0.4+/-6.9% increase for M and E) during the first minute of running appeared to be more adverse (p<0.05) for M than E. The mechanical changes between pre- and postcycling exercise were similar among the two groups at the 6th minute, suggesting that the mechanical alterations due to a cycling fatigue in M are brief. CONCLUSIONS: Since the needs to run efficiently immediately after cycling are associated with performance in triathlon, the results of the present study have practical implications for training.